(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article highlights the analysis of the basic definitions and concepts of religious identity, and in particular, the category of identity itself. Religious identity as a component of the social identity acts as the cultural code, which is transmitted from generation to generation to determine the moral and social norms.The analysis of the major religious identity researches shows us that the religion acts as the important content in the identification process. Processes of globalization have opened borders for new valuable reference points in society, particularly concerning with the new forms of «Islamic», «Christian» and a number of other identities, unlike previously familiar for us traditional forms. The contemporary identification processes represent us that adherence to this or that religion does not determine the location of a person in this world and socium, both in geographical and ethnic aspect, since the link between the religious (confessional) identity and ethnicity may be located in completely different areas.